2008
DOI: 10.1124/jpet.108.141887
|View full text |Cite
|
Sign up to set email alerts
|

Clotrimazole Ameliorates Intestinal Inflammation and Abnormal Angiogenesis by Inhibiting Interleukin-8 Expression through a Nuclear Factor-κB-Dependent Manner

Abstract: Increased interleukin (IL)-8 plays an important role not only in activation and recruitment of neutrophils but also in inducing exaggerated angiogenesis at the inflamed site. In the present study, we investigated the fact that clotrimazole (CLT) inhibits intestinal inflammation, and the inhibitory action is mediated through suppression of IL-8 expression. In the trinitrobenzene sulfonic acid (TNBS)-induced rat colitis model, CLT dose-dependently protected from the TNBS-induced weight loss, colon ulceration, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…GenBank accession numbers for these sequences used are listed in Table 2. avian IL-8. In mammals, the ELR motif was known to be responsible for promoting angiogenesis, one of the most important abilities of this group of chemokines [25][26][27]. Chicken IL-8 possessed an ELR motif and was shown to involve in receptor binding in human or chicken IL-8 [4,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GenBank accession numbers for these sequences used are listed in Table 2. avian IL-8. In mammals, the ELR motif was known to be responsible for promoting angiogenesis, one of the most important abilities of this group of chemokines [25][26][27]. Chicken IL-8 possessed an ELR motif and was shown to involve in receptor binding in human or chicken IL-8 [4,28].…”
Section: Discussionmentioning
confidence: 99%
“…NF-kB is a major transcription factor that regulates genes responsible for both the innate and the adaptive immune response. It has been reported that activation of NF-kB and its dependent genes may be one of the important pathways used by IL-8 during inflammation angiogenesis [27]. c-Rel, a number of NFkB family and predominantly expressed in immune cells, could regulate gene transcription in T cells and was implicated in leukocyte trafficking, particularly that related to Th1-mediated inflammation [36].…”
Section: Discussionmentioning
confidence: 99%
“…The method used to establish the model of TNBS-induced rat colitis was adapted from that described previously (46). Sprague-Dawley rats (age, 7 to 8 weeks) were purchased from Samtaco bio Korea (Osan, South Korea).…”
Section: Methodsmentioning
confidence: 99%
“…It contains a 1265 bp promoter region, in which several putative binding sites for TATA box, NF-B, C/EBP ␤, c-Rel (3 sites), oct-1, ARP-1 (2 sites), HLF and HSF are present, suggesting that the transcription of turtle SAA may be regulated by multiple transcription factors in inflammatory response. Among these factors, NF-B is a major transcription factor that regulates the genes responsible for both the innate and the adaptive immune response (Thapa et al, 2008); c-Rel, a member of NF-B family, is predominantly expressed in immune cells. It regulates gene transcription in T cells and is implicated in leukocyte trafficking, is particularly related to Th1-mediated inflammation (Bunting et al, 2007).…”
Section: Turtle Saa Homologue Is Highly Conserved and Clusters Togetmentioning
confidence: 99%